Ranking Economics and Econometrics ISI Journals by Quality Weighted Citations - Chia-Lin Chang; Michael McAleer (Tinbergen Institute, 2014)
The paper analyses academic journal quality and impact using quality weighted citations that are based on the widely-used Thomson Reuters ISI Web of Science citations database (ISI). A recently developed Index of Citations Quality (ICQ), based on quality weighted citations, is used to analyse the top 276 Economics and top 10 Econometrics journals in the ISI Economics category using alternative quantifiable Research Assessment Measures (RAMs). It is shown that ICQ is a useful additional measure to the 2-Year Impact Factor (2YIF) and other well known RAMs available in ISI for the purpose of evaluating journal impact and quality, as well as ranking, of Economics and Econometrics journals as it contains information that has very low correlations with the information contained in alternative well-known RAMs. Among other findings, the top Econometrics journals have some of the highest ICQ scores in the ISI category of Economics.
Keywords: C18; C81; Y10; 330; Research assessment measures; Impact factors; Eigenfactor; Article Influence; Quality weighted citations; Index of citations quality; Economics journal rankings